Increase the glyde path diameter improves the centering ability of F6 Skytaper - Troiano, Giuseppe (Eur J Dent, 2018)
OBJECTIVE: The aim of this study was to assess the impact of glide path preparation, performed with PathGlider 0.15 (Komet Brasseler GmbH & Co., Lemgo, Germany) and PathGlider 0.20 (Komet Brasseler GmbH & Co., Lemgo, Germany), on the centering ability of 25-size F6 Skytaper in J-shape simulated root canals, compared with no glide path executed. MATERIALS AND METHODS: Sixty J-shaped ISO 15 0.02 taper endo training blocks (Dentsply Maillefer) were assigned to three groups (n = 20 for each group). Photographic images were taken on endoblocks before and after shaping procedures. After superimposition, the software AutoCAD 2013 (Autodesk Inc., San Rafael, USA) was used for record the centering and shaping ability at 9 different levels from the apex. RESULTS: Shaping procedures including the using of PathGlider 0.20 resulted in a lower amount of resin removed and in a clear improvement of centering ability of the Skytaper 0.25 at almost all reference point levels. CONCLUSIONS: Within the limitations of this study, it could be concluded that the glide path procedure, performed with the PathGlider 0.20 before the shaping with 25-size F6 Skytaper, might determine a lower amount of resin removed and a better centering ability compared with the groups without glide path procedure and those treated with PathGlider 0.15.